MENINGKATKAN KEMAMPUAN KOORDINASI MATA DAN TANGAN PADA ANAK TUNAGRAHITA SEDANG - Tasnila - - (Jurnal Penelitian Pendidikan Khusus, 2012)
This research aim to to: proving technique efectivity baste comisole improve ability of eye movements coordination and hand embisil of child class D1/C1 in SLB YAPPAT Lubuk Sikaping Pasaman. This research use approach of Single Subject Reaserch (SSR) with A-B desain. Its Subject Research is embisil of child X. The goals size measure of him that is how many hole which can be basted by child from 15 provided hole during 10 minute. Data the obtained to be to be processed in grafict. Result of research indicate that eye movements coordination and hand mount after given technique baste clothes. This proven at phase of baseline (A) ability of eye movements coordination and child hand in basting only four hole which can be sewed during 10 minute. After given by intervention (B) technique baste clothes, eye movements coordination and hand mount namely child have finished 15 hole in 10 minute. Thereby can be concluded that technique baste clothes can improve eye movements coordination and hand embisil of child class D.1/C1 SLB YAPPAT Lubuk Sikaping. Thereby suggested to researcher and teacher hereinafter so that using technique baste other to train eye movements coordination and hand embisil of child.